Comprehensive analysis of glycosphingolipids in biological samples using HPLC/MS - Hořejší, Karel (Univerzita Pardubice, 2024)
Lipids are biomolecules found in all living organisms, where they have several vital functions. Lipids are the subject of lipidomics, a subgroup of metabolomics, which represents one of the so-called ?omics? disciplines that also includes genomics, proteomics, and glycomics. Dysregulation of lipid metabolism can reflect the onset of various diseases including cancer, therefore, lipidomic analysis can provide valuable information about ongoing pathophysiological processes in humans. The theoretical part provides an extensive overview of glycosphingolipids, including their biosynthesis, structure complexity, classification, nomenclature, and various biological functions in association with pathophysiological conditions as a hallmark of a variety of diseases, for example, cancer. Special attention is also paid to the sample preparation and key analytical methods for their identifications and quantitation. Qualitative and quantitative approaches are discussed as well, along with their advantages and limitations. The experimental part deals with the development, optimization, and application of analytical methods for the analysis of especially glycosphingolipids in biological samples, such as human plasma/serum and tissues using chromatographic techniques coupled to mass spectrometry. Special attention is devoted to in-depth structural characterization and qualitative glycosphingolipids profiling using a lipid class separation approach (HILIC). Correspondingly, glycosphingolipid profiling is used to expand the database of lipids that are routinely analyzed, and for the mutual comparison of healthy volunteers and cancer patients. Therefore, the analysis of glycosphingolipids has the potential to facilitate the discovery of novel biomarkers for the early detection of various diseases.
Komplexní analýza glykosfingolipidů v biologických vzorcích pomocí HPLC/MS
Keywords: lipidomika; glykosfingolipidy; plasma; pankreatické tkáně; extrakce; přečištění; strukturní charakterizace; tandemová hmotnostní spektrometrie; hydrofilní interakční kapalinová chromatografie; lipidomics; glycosphingolipids; plasma; pancreatic tissue; extraction; purification; structural characterization; tandem mass spectrometry; hydrophilic interaction liquid chromatography